Repeated Restraint Stress Led to Cognitive Dysfunction by NMDA Receptor-Mediated Hippocampal CA3 Dendritic Spine Impairments in Juvenile Sprague-Dawley Rats - Sun, Dong-sheng; Zhong, Gang; Cao, Hong-Xia; Hu, Yu; Hong, Xiao-Yue; Li, Ting; Li, Xiao; Liu, Qian; Wang, Qun; Ke, Dan; Liu, Gong-ping; Ma, Rong-Hong; et al. (Frontiers in Molecular Neuroscience, 2020)
Although numerous studies have indicated that chronic stress causes cognitive dysfunction with the impairment of synaptic structures and functions, the relationship between cognitive deficits induced by repeated restraint stress and the level of NMDA-receptor in the subregion of hippocampus is still vague until now. In this study, 3-week-old male Sprague-Dawley rats were exposed to repeated restraint stress for 7 days consecutively, their cognitive functions were evaluated through behavioral tests, and then they were sacrificed for electrophysiological, morphological, and biochemical assays. Chronic repeated restraint stress led to cognitive and electrophysiological impairments, with a reduced density of dendritic spines. We also found that the protein level of NMDA receptors increased only in the hippocampal CA3 region. Nevertheless, repeated restraint stress-induced cognitive and synaptic dysfunction were effectively reversed byRo25-6981, an inhibitor of the GluN2B receptor. These findings suggest that repeated restraint stress-induced synaptic and cognitive deficits are probably mediated through NMDA receptor.